Dependence on Humidity and Aerosol Composition of the Gas-particle Partitioning of Weakly and Moderately Polar VOCs - Jeonghyeon Ahn; Guiying Rao; Eric P. Vejerano (Aerosol and Air Quality Research)
Abstract Volatile organic compounds (VOCs) dominate the class of pollutants that accumulate in the atmosphere and indoors. Assessing the gas-particle partitioning of VOCs is important to determine their fate, transport, and adverse health impacts. This work is a companion to our earlier study on the temperature dependence of VOC partitioning. Here, we report our measurement of the gas-particle partition coefficient (Kp) for weakly polar (trichloroethylene, TCE) and moderately polar (n-butanol, n-BuOH) VOCs under varying relative humidity (RH) levels onto organic and inorganic aerosols. Kp of TCE was four to five orders of magnitude lower than those of n-BuOH. Results suggest preferential sorption of the VOCs onto inorganic aerosol particles than onto organic aerosol particles. Kp values for both TCE and n-BuOH decreased as RH levels increased; the Kp for both VOCs declined sharply at an RH > 35% onto inorganic aerosol particles, whereas the Kp declined slowly onto organic aerosol particles. Partitioning of the VOCs onto organic aerosol particles was less dependent on RH levels while partitioning onto inorganic aerosol particles was important only at low RH levels. At lower RH, partitioning proceeded by adsorbing onto the aerosol particles. In contrast, at higher RH, the extremely low mass fraction of the VOCs, absorbed onto the aerosol particle’s bulk by dissolving into the aqueous phase. For organic aerosol particles, partitioning may be dominated by adsorption at all RH levels. At increasing RH levels, both VOCs partitioning onto in/organic aerosol particles exhibited similar behavior (exponential) consistent to those observed for 1,2-dichlorobenzene, therefore, insensitive to the polarity. However, at a similar RH level, polarity affects the mass fraction of the VOCs that sorbed onto the aerosol particles.